Aortomesenteric Angle and Distance in Relation to Body Mass Index: A Descriptive Cross-Sectional Study Using Computed Tomography (Nepalese Journal of Radiology, 2025)
Introduction: Superior mesenteric artery syndrome (SMAS) is a rare cause of upper gastrointestinal obstruction resulting from compression of the third part of the duodenum between the abdominal aorta and the superior mesenteric artery (SMA). Reduction in aortomesenteric angle (AMA) and aortomesenteric distance (AMD), often related to decreased body mass index (BMI), and predisposes individuals to this condition. This study aimed to assess the relationship between BMI, AMA, and AMD using contrast-enhanced computed tomography (CT) imaging in the Nepalese population.Methods: A descriptive cross-sectional study was conducted involving 324 patients undergoing abdominal contrast-enhanced CT scans at Patan Academy of Health Sciences, Nepal. AMA and AMD were measured on sagittal and axial reconstructions, respectively. Participants were categorized based on BMI according to the WHO classification. Correlations among BMI, AMA, and AMD were analyzed using Pearson’s correlation coefficient.Results: Among 324 patients (220 males, 104 females; mean age 46.2 ± 14.7 years), the average BMI was 26.9 ± 4.5 kg/m². The mean AMA and AMD were 56.3° ± 16.4° and 15.4 ± 5.2 mm, respectively. BMI showed a significant positive correlation with AMA (r = 0.19, p < 0.01) and AMD (r = 0.15, p = 0.02). A strong correlation was noted between AMA and AMD (r = 0.64, p < 0.001).Conclusions: We can infer that BMI significantly influences aortomesenteric angle and aortomesenteric distance. The findings can assist in the CT-based evaluation of SMAS and provide reference data tailored for the South Asian population.